2018
DOI: 10.1084/jem.20170484
|View full text |Cite
|
Sign up to set email alerts
|

JDP2: An oncogenic bZIP transcription factor in T cell acute lymphoblastic leukemia

Abstract: Mansour et al. demonstrate that JDP2, a bZIP transcription factor, is overexpressed in patients with high-risk T cell acute lymphoblastic leukemia (T-ALL). JDP2 initiates T-ALL in a zebrafish model and leads to steroid resistance in vivo through direct regulation of MCL1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 73 publications
(105 reference statements)
2
28
0
Order By: Relevance
“…In the context of pediatric cancer, one of the most valuable aspects of the fish model is the access it provides to a range of developmental time windows and tissue lineages, some only present during early development and absent at the adult stage. Pioneering work modeling T-cell leukemias in fish ( Langenau et al, 2003 ) enabled use of the system to discover novel leukemia genes such as ARID5B ( Leong et al, 2017 ) and JDP2 ( Mansour et al, 2018 ). A transgenic model of neuroblastoma ( Zhu et al, 2012 ) highlighted the role of developmental apoptosis as an oncogene-induced antitumor response.…”
Section: Modeling Developmental Mechanisms Of Childhood Cancermentioning
confidence: 99%
“…In the context of pediatric cancer, one of the most valuable aspects of the fish model is the access it provides to a range of developmental time windows and tissue lineages, some only present during early development and absent at the adult stage. Pioneering work modeling T-cell leukemias in fish ( Langenau et al, 2003 ) enabled use of the system to discover novel leukemia genes such as ARID5B ( Leong et al, 2017 ) and JDP2 ( Mansour et al, 2018 ). A transgenic model of neuroblastoma ( Zhu et al, 2012 ) highlighted the role of developmental apoptosis as an oncogene-induced antitumor response.…”
Section: Modeling Developmental Mechanisms Of Childhood Cancermentioning
confidence: 99%
“…myeloid leukemia (AML) and T-ALL [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For T-ALL in particular, zebrafish models have been highly informative, advancing our understanding of T-ALL genetics, pro-and anti-oncogenic interactions between different genes and pathways, tumor heterogeneity, leukemia stem cells, and in screens for new therapeutics [28,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Research Perspectivementioning
confidence: 99%
“…As the rag2 promoter is transcriptionally active during the development of T-,cells as well as B-cells, it has recently been shown that B-cell acute lymphoblastic leukemia (B-ALL) could also occur in this zebrafish T-ALL model [95]. Thus far, various zebrafish T-ALL models have been developed based on the constitutive expression of the human intracellular domain of NOTCH1 , mouse Myc [91], mouse Akt2 [92], zebrafish jdp2 [96] and human ARID5B [97] genes. Besides these transgenic zebrafish T-ALL models, Frazer and colleagues identified three zebrafish mutants, Hulk ( hlk ), Shrek ( srk ) and Oscar the grouch ( otg ) that develop transplantable T-ALL using a forward genetic approach [98].…”
Section: Zebrafish As Model System For T-cell Diseasesmentioning
confidence: 99%